Love in Vain : A Vision of Robert Johnson - Greenberg, Alan (Book collections on Project MUSE., 2012)
Robert Johnson was undoubtedly the most outstanding of the Mississippi Delta blues musicians and also one of the first inductees into the Rock and Roll Hall of Fame, but his short life remains steeped in mystery and wrapped in some of the most enduring legends of modern music. Love in Vain is Alan Greenberg's remarkable, highly acclaimed, and genre-defying screenplay and is widely considered to be one of the foremost books on Robert Johnson's life and legacy and an extraordinary exercise in American mythmaking. Newly revised and complete with extensive historical notes on Johnso.